1993
DOI: 10.1007/bf01316508
|View full text |Cite
|
Sign up to set email alerts
|

Role of bile acids and metabolic activity of colonic bacteria in increased risk of colon cancer after cholecystectomy

Abstract: Since the metabolic activity of the colonic flora plays a definite role in colon cancer and an increased incidence of this disease is reported after cholecystectomy, we studied the metabolic activity of the colonic flora in a group of postcholecystectomy patients and matched controls by measuring, as representative end products of the bacterial metabolism, their fecal bile acids (BA), fecal 3-methylindole (SK) and indole (IN), and respiratory methane and hydrogen. Patients had significantly higher SK and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 46 publications
4
59
0
4
Order By: Relevance
“…The stool samples we used had been stored at Ϫ80°C for 10 to 20 years, and to our knowledge, there is no published literature regarding indole stability under such conditions. However, our stage 1 indole levels were consistent with values from control individuals in two earlier studies using freshly collected stool samples (43,44), although direct comparisons could not be made since stool samples were prepared, extracted, and tested by different techniques. Further, all of the stool samples we used were stored under the same conditions and the indole concentrations in samples from 1993 to 1998 were no different from those in samples from 1999 to 2004.…”
Section: Discussionsupporting
confidence: 48%
“…The stool samples we used had been stored at Ϫ80°C for 10 to 20 years, and to our knowledge, there is no published literature regarding indole stability under such conditions. However, our stage 1 indole levels were consistent with values from control individuals in two earlier studies using freshly collected stool samples (43,44), although direct comparisons could not be made since stool samples were prepared, extracted, and tested by different techniques. Further, all of the stool samples we used were stored under the same conditions and the indole concentrations in samples from 1993 to 1998 were no different from those in samples from 1999 to 2004.…”
Section: Discussionsupporting
confidence: 48%
“…Few studies have reported indole concentrations in the stools of healthy adults. Gas chromatographic analysis of indole and 3-methylindole (skatole) from the fecal samples of 84 patients with colorectal cancers, 20 postsurgical cholecystectomy patients, and 15 healthy control patients reported concentrations in the 5-to 156-g/g range for the two molecules (29,30). These values are roughly consistent with what we found but cannot be compared directly since the data were expressed per gram (dry weight) of feces.…”
Section: Discussionsupporting
confidence: 81%
“…The continuous exposure of the gut to higher levels of metabolic products, such as biliary acids, undigested fat, and other end products of the colonic microflora (e.g. 3-methylindole), in cholecystectomised patients (Zuccato et al, 1993) might further elevate colon cancer risk. Animal models suggest that colon cancer risk increases with higher levels of secondary bile acids (Morvay et al, 1989).…”
Section: Discussionmentioning
confidence: 99%